Is Planckian Discreteness Observable in Cosmology? - Gabriel R. Bengochea; Gabriel León; Alejandro Perez (Universe)
A Planck scale inflationary era—in a quantum gravity theory predicting discreteness of quantum geometry at the fundamental scale—produces the scale-invariant spectrum of inhomogeneities with a very small tensor-to-scalar ratio of perturbations and a hot big bang leading to a natural dark matter genesis scenario. Here, we evoke the possibility that some of the major puzzles in cosmology would have an explanation rooted in quantum gravity.